(untitled) (EDUCATION IN THE 21ST CENTURY, 2023)
The article presents the rationale of the theoretical and practical aspects of the formation and development of the basic household and labor skills in children with a deep degree of mental retardation. The literary evidence and experience indicate that the function and significance of the creation of simple daily life and labor skills and abilities of self-service and self-orientation in microspace is tremendously growing in the general system of education, training and development of children with a deep degree of mental retardation. In addition, the experience of work reveals that an insufficiently consistent description of the theoretical and practical aspects of the formation and growth of children with a severe degree of mental retardation greatly complicates the effective organization and execution of practical work of those issues with this contingent of children in a specialized orphanage. The foregoing defines the necessity for a deep and systematic study of this issue, the development and substantiation of theoretical and practical aspects of the formation and development of basic social, household and labor skills and abilities of vital importance. This will serve as the basis for the correct and effective organization and implementation of practical exercises and activities to address these important tasks.